A new epiphyllous species of Cololejeunea (Lejeuneaceae, Marchantiophyta) from China - Wang, Jian; Zhou, Ling-Yan; Zhu, Rui-Liang (Phytotaxa, 2014)
Cololejeunea sublatistyla J.Wang & R.L.Zhu sp. nov. is described and illustrated from Jianfengling National Nature Reserve, Ledong Co., Hainan Province, China. The new species is similar to C. latistyla R.L.Zhu but differs mainly in its rectangular-ovate, triangular or triangular-ovate leaf lobules, the smaller stylus (9–14 cells long and 2–3 cells wide), and female bract lobule without any lobular teeth.